2016
DOI: 10.1111/epi.13592
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of FDGPET hypometabolism and SEEG epileptogenicity mapping in patients with drug‐resistant focal epilepsy

Abstract: SummaryObjectiveInterictal [18F]fluorodeoxyglucose–positron emission tomography (FDG‐PET) is used in the presurgical evaluation of patients with drug‐resistant focal epilepsy. We aimed at clarifying its relationships with ictal high‐frequency oscillations (iHFOs) shown to be a relevant marker of the seizure‐onset zone.MethodsWe studied the correlation between FDG‐PET and epileptogenicity maps in an unselected series of 37 successive patients having been explored with stereo‐electroencephalography (SEEG).Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
(82 reference statements)
4
30
1
Order By: Relevance
“…A recent study, using stereo-EEG, also found a poor correlation between hypometabolic cortex and iHFOs in patients with extratemporal seizure foci [Lamarche et al, 2016]. Despite the different PET analytic approaches, both those previous and our current results demonstrated a mismatch between hypometabolic and epileptogenic cortex, which appears to be present regardless of age or epilepsy duration.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…A recent study, using stereo-EEG, also found a poor correlation between hypometabolic cortex and iHFOs in patients with extratemporal seizure foci [Lamarche et al, 2016]. Despite the different PET analytic approaches, both those previous and our current results demonstrated a mismatch between hypometabolic and epileptogenic cortex, which appears to be present regardless of age or epilepsy duration.…”
Section: Discussioncontrasting
confidence: 47%
“…Two previous studies from our group have used an asymmetry-based approach to compare the performance of FDG-PET against ECoG-defined SOZ in small pediatric groups with epilepsy surgery [Alkonyi et al, 2009;Juh asz et al, 2000]. A recent study, using stereo-EEG, also found a poor correlation between hypometabolic cortex and iHFOs in patients with extratemporal seizure foci [Lamarche et al, 2016]. Despite the different PET analytic approaches, both those previous and our current results demonstrated a mismatch between hypometabolic and epileptogenic cortex, which appears to be present regardless of age or epilepsy duration.…”
Section: Discussionmentioning
confidence: 98%
“…Among 490 SEEG-informed patients who underwent resective surgery from nine studies, 310 patients (61.0%, 95% CI = 60.5-61.4%) were seizure-free. 15,16,22,23,27,28,32,33,49 Of the 953 SDE-informed patients who underwent resective surgery from 21 studies, 564 patients (56.4%, 95% CI = 55.7-57.1%) were seizurefree. 18,20,21,24,25,[35][36][37][38][39][40][41][42][43][44][45]47,48,[50][51][52] Therefore, SEEG-informed surgical resections have associations that suggest better seizure freedom outcomes than SDE-informed surgical resections (WMD = +5.8%, 95% CI = 4.7-6.9%, P = .001).…”
Section: Epileptic Surgery and Outcomesmentioning
confidence: 99%
“…[3][4][5][6] The costefficiency of 18 FDG-PET has long been recognized, and the wider availability of postacquisition processing techniques has increased its yield in surgical planning. 17,18 Furthermore, the findings of recent 18 FDG-PET and functional connectivity studies have been convergent in demonstrating the role of 18 FDG-PET as a metabolic biomarker of the extent of the epileptic network dysfunction. [12][13][14][15][16] There has been a growing body of evidence suggesting that the extent of the metabolic compromise correlates with the distribution of ictal EEG discharges.…”
mentioning
confidence: 93%
“…[12][13][14][15][16] There has been a growing body of evidence suggesting that the extent of the metabolic compromise correlates with the distribution of ictal EEG discharges. 17,18 Furthermore, the findings of recent 18 FDG-PET and functional connectivity studies have been convergent in demonstrating the role of 18 FDG-PET as a metabolic biomarker of the extent of the epileptic network dysfunction. 19,20 It has also been suggested that hypometabolic changes affecting the contralateral (CTL) temporal lobe (TL) may impact on seizure outcomes in patients with drug-resistant MTLE.…”
mentioning
confidence: 93%